The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s12917-021-03013-6
|View full text |Cite
|
Sign up to set email alerts
|

First detection and phylogenetic analysis of porcine circovirus 3 in female donkeys with reproductive disorders

Abstract: Background PCV3 is a pathogen associated with porcine dermatitis and nephropathy syndrome (PDNS)-like clinical signs, reproductive failure, and cardiac and multiorgan inflammation, which was newly identified in 2016 in sows in USA. Recently, PCV3 has also been identified from several non-porcine species like (cattle, dog, wild boar, deer, mice and ticks). However, PCV3 infection in donkey is not well established. Since 2019, 300 blood samples were collected from female donkey, which was charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Two studies on PCV2 infection in species other than pigs showed that PCV2 might be related to reproductive failure in raccoon dogs and foxes ( 31 , 32 ). PCV3 infection is associated with reproductive failure in donkeys ( 33 ). PCV4 was identified to be pathogenic to piglets by inoculation of piglets with the virus rescued from infectious clones ( 23 ).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies on PCV2 infection in species other than pigs showed that PCV2 might be related to reproductive failure in raccoon dogs and foxes ( 31 , 32 ). PCV3 infection is associated with reproductive failure in donkeys ( 33 ). PCV4 was identified to be pathogenic to piglets by inoculation of piglets with the virus rescued from infectious clones ( 23 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, while wild suids could be considered a reservoir host for this virus, because of the low infection prevalence in wild ungulates, the role of these animals in the maintenance of PCV-3 in wildlife remains unclear ( Turlewicz-Podbielska et al., 2022 ). Finally, this virus has also been identified in blood samples of dogs with various symptoms ( Zhang et al., 2018 ), donkeys with reproductive disorders ( Wang et al., 2021 ), and laboratory mice ( S. Jiang et al., 2019 ). Interestingly, the virus was also identified in ticks collected from PCV‐3 negative deer, suggesting that vector-born transmission should be investigated as a potential transmission route ( Franzo et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The increasing population of wild boar, leading to more interactions with domestic pigs, could facilitate the transmission of PCV3 from wild boar to domestic pigs [ 72 ]. Furthermore, interspecies transmission of PCV3 from pigs to other animals might also be possible, as revealed by different studies [ 206 , 207 ].…”
Section: Factors Associated With Clinical Manifestation Of Pcv-associ...mentioning
confidence: 99%